Overview of credit management & exposure on ready-made garments sector: a study on United Commercial Bank Limited - Hossain, Mohammad Palash (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.